Analisis dan Evaluasi Jabatan pada Perusahaan Tekstil - Sukwadi, Ronald; Oktevany, Livia (Jurnal Rekayasa Sistem Industri, 2016)
This research presents job analysis and evaluation in order to design salary structure of a textile company. Preliminary interview, questionnaire, observation and focus group discussions were applied for job analysis. In addition, a point factor system and analytical hierarchy process methods were used for doing job evaluation. Job description and job specification and basic salary of each job were produced in this study.Â